On a Magical Mystery Tour of Green Insecticide Research: Current Issues and Challenges - Giovanni Benelli (Molecules, 2020)
The Editorial outlines recent research advances in green insecticide research. Particular attention is devoted to studies shedding light on the modes of action and non-target toxicity of natural substances of plant origin. Research focusing on the development of new formulations (including those relating to nano-objects) to magnify the effectiveness and stability of green insecticides in the field represents key advances. Herein, a carefully reviewed selection of cutting edge articles about green pesticide development recently published in Molecules is presented. The impact of sub-lethal doses of green insecticides on insect behavioral traits is still overlooked, representing a timely challenge for further research.